2010
DOI: 10.4236/health.2010.26094
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity pattern of common bacterial pathogens in NICU and neonatal ward in Hamedan province of Iran

Abstract: Bacterial pathogens and drug resistance are different in hospitals of each country. In this study we determined bacterial path- ogens and drug sensitivity in the neonatal ward and neonatal intensive care unit (NICU) in Ekbatan hospital in Hamedan. This cross-sectional descriptive study was done on 1150 hospitalized neonates in neonatal and NICU wards of Ekbatan hospital of the Hamadan university of medical sciences from September 2004 to September 2006. Blood, cerebrospinal fluid (CSF), urine, stool, eye excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
4
7
0
Order By: Relevance
“…Based on Monsef and Eghbalian research, S. saprophyticus was the most Gram-positive isolated bacteria in the urine culture; this is similar to the results of the present research (11). However, the antibiotic susceptibility pattern was opposite so that in our research vancomycin and nitrofurantoin were the most effective antibiotics, and cotrimoxazole was the less effective antibiotic for S. saprophyticus while in the study of Monsef and Eghbalian these bacteria were sensitive to co-trimoxazole and resistant to vancomycin.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Based on Monsef and Eghbalian research, S. saprophyticus was the most Gram-positive isolated bacteria in the urine culture; this is similar to the results of the present research (11). However, the antibiotic susceptibility pattern was opposite so that in our research vancomycin and nitrofurantoin were the most effective antibiotics, and cotrimoxazole was the less effective antibiotic for S. saprophyticus while in the study of Monsef and Eghbalian these bacteria were sensitive to co-trimoxazole and resistant to vancomycin.…”
Section: Discussionsupporting
confidence: 76%
“…Likewise, many scientists reported E. coli as common pathogenic isolates in UTI (12,(19)(20)(21); however, in some geographic regions such as Nigeria (Ebonyi State university teaching hospital, Children's emergency unit, age group between birth to five years old) Klebsiella spp was reported as the main factor of UTI in children (22). In Iran, Monsef and Eghbalian and Mirsoleymani et al reported Klebsiella spp as the second factor for UTI besides E. coli (Ekbatan hospital of the Hamadan University of Medical Sciences, neonatal and neonatal intensive care unit, age group between one to 30 days), as shown in our study (11,16). Furthermore, some scientists indicated that Klebsiella spp is more isolated from boys with UTIs; it is hypothesized that etiological agents of urinary tract infection vary between both genders (23).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Most common organisms found in our study were E. coli (40), Klebsiella (16) and Pseudomonas (17), which is in accordance with other studies done where Klebsiella and E.coli were the most common organisms. 18,19 In our study, No.…”
Section: 15mentioning
confidence: 97%